Mapping Competencies: A Profound Analysis of Semester 1 Cadets at a Premier Maritime Institute - Panderaja Soritua Sijabat; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This academic exploration delves into the nuanced competencies and dynamics shaping the academic journey of Semester 1 cadets at a distinguished Maritime Institute. Focusing on computer literacy, technological proficiency, and sociocultural influences, our qualitative descriptive approach seeks to unveil the intricate dimensions of contemporary maritime education. The assessment of computer literacy reveals varying competencies, urging the need for a tailored curriculum. While basics like office software and digital navigation are strong, disparities in data analysis proficiency call for targeted interventions. The implications highlight the necessity for a stratified curriculum, ensuring a comprehensive skill set in line with modern maritime demands. Cadets overwhelmingly endorse technology's role in enhancing education, signalling a paradigm shift. Positive attitudes towards online resources, digital simulations, and e-learning platforms advocate for an institutional embrace of cutting-edge tools. Recommendations focus on faculty development and increased technology integration, promising an enriched pedagogical landscape. The exploration of sociocultural influences uncovers a delicate balance between tradition and the necessity of English proficiency. Nuanced strategies are essential to integrate diverse cultural backgrounds. Recommendations call for cultural awareness initiatives and language support programs, aligning the institution with the global orientation of maritime education. In qualitative insights, cadets express a collective desire for a more intentional curriculum, particularly in incorporating cultural perspectives. This aligns with the broader scholarly discourse advocating for holistic education. Proposed avenues include workshops, seminars, and collaborations with cultural experts, providing a roadmap for curriculum development congruent with the diverse needs of Semester 1 cadets. This research, rooted in rigorous academic inquiry, serves as a guide for the Maritime Institute, steering its trajectory towards producing technologically adept professionals who are equally culturally astute, ready to navigate the complex global maritime landscape.